Consumer Perceived Risk in Online Shopping: A Study on Rural Customers of Karnataka State (International Journal of Food and Nutritional Sciences, 2022)
Online shopping has drastically transformed the retail landscape, providing consumers with unprecedented convenience, accessibility, and variety. The ability to shop from the comfort of one's home, access a wider range of products than what might be available in local stores, and benefit from competitive pricing are among the key advantages that have driven the growth of e-commerce. With the rise of internet connectivity and the proliferation of digital devices, more consumers are turning to online platforms for their shopping needs, ranging from daily essentials to luxury items.Perceived risks in online shopping can be classified into several categories: financial risk, product risk, security risk, delivery risk, and privacy risk. Each of these risks represents a different aspect of the online shopping experience that can cause anxiety or concern for consumers.Understanding consumer behavior and perceptions is vital for businesses operating in the ecommerce space. Addressing perceived risks can lead to a more secure and satisfying shopping experience, fostering greater consumer loyalty and encouraging repeat business. For example, enhancing website security, providing accurate product descriptions and high-quality images, and offering reliable customer service can significantly reduce perceived risks. Clear return policies and efficient delivery services can also boost consumer confidence.This study involves a comprehensive survey to understand perceptions of risk among online shoppers. The study is designed to capture respondents' demographic profiles, their online shopping habits, and their perceptions of various risks associated with online shopping. It aims to examine the steps consumers take to mitigate these risks involved in online shopping process. The attempts to explore the level of trust consumers have in online retailers and the influence of online reviews and ratings on their purchasing decisions.